2022
DOI: 10.7454/ihpa.v7i3.6013
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Need for Legal Protection for Doctors in Teleconsultation Services Towards the Covid-19 Endemic in Indonesia

Abstract: Teleconsultation is a form of telemedicine that has developed rapidly during the COVID-19 pandemic. Clinical teleconsultation provides remote clinical consultation services to assist in establishing a diagnosis, and/or providing treatment considerations/advice. There are several issues in telemedicine, including ethical and legal issues. This study aims to find ethical and legal issues related to teleconsultation services after the COVID-19 pandemic. This research uses normative legal research methods. The law… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…The findings have suggested that ChatGPT could impact healthcare teleconsultations in different ways, especially in managing their activities and operations, reducing work burden, increasing awareness, and personal development. Studies 30,31 observed that the physicians need to be aware of various information in healthcare, especially in treatments, medications, standards, legal and regulatory policies. It can be observed from the findings that many participants identified the positive aspect of ChatGPT in providing informational support.…”
Section: Discussionmentioning
confidence: 99%
“…The findings have suggested that ChatGPT could impact healthcare teleconsultations in different ways, especially in managing their activities and operations, reducing work burden, increasing awareness, and personal development. Studies 30,31 observed that the physicians need to be aware of various information in healthcare, especially in treatments, medications, standards, legal and regulatory policies. It can be observed from the findings that many participants identified the positive aspect of ChatGPT in providing informational support.…”
Section: Discussionmentioning
confidence: 99%
“…This technical regulation would be best regulated in the standard operational procedures of the hospital, where it certainly cannot in any way go against the higher regulations, yet perfectly reflects the telemedicine services used in such hospital. [21] Norms to be strongly upheld within the hospital's standard operational procedures are the protection of every individual's data and information and data and information management and provision. A standard operational procedure is a delegation as regulated in Article 291 (4) of the Health Law 17/2023 and is to be determined by the management of the Healthcare Service Facility.…”
Section: Ius Constituendum Telemedicine Hospital Post Covid 19 and He...mentioning
confidence: 99%